Kedudukan Hukum Wanita Haid dan Orang Junub Memasuki Masjid dan Membaca Al-Qur'an: The Legal Status of Menstruating Women and Those in a State of Major Ritual Impurity in Entering Mosques and Reciting the Qur'an - Rafid Abas (Fenomena, 2005)
The legal status of menstruating women and sexually impure individuals (junub) regarding mosque entry and Qur'anic recitation remains contested among Islamic scholars, with some prohibiting such acts and others permitting them. This discrepancy stems from differing methodological approaches to evaluating scriptural evidence. This study aims to critically reexamine the legal foundations of these prohibitions by comprehensively analysing relevant Qur'anic verses and hadiths. Using a qualitative library research method with content and comparative analyses, the study scrutinises the chains of transmission (sanad) and texts (matan) of hadiths commonly cited as evidence for prohibition. The findings reveal that Qur'anic verses (e.g., QS. al-Nisa': 43) explicitly permit junub individuals to pass through mosques without addressing Qur'anic recitation, while no clear Qur'anic prohibition exists for menstruating women. Critically, hadiths invoked to prohibit these acts contain significant weaknesses, including narrators classified as majhul (unknown), matruk (abandoned), or unreliable, such as Aflat bin Khalifah and Abdillah bin Salamah. Consequently, these hadiths are deemed weak (da'if) and unsuitable as legal evidence. The study concludes that menstruating women may enter mosques and recite the Qur'an, while junub individuals may only pass through mosques. It recommends that scholars prioritise authentic scriptural sources and rigorously apply the principle of al-jarh muqaddamun ala al-ta'wil (criticism precedes praise) when evaluating contradictory narrations. Status hukum wanita haid dan orang junub terkait masuk masjid dan membaca al-Qur'an masih menjadi perdebatan di kalangan ulama, sebagian melarang dan sebagian membolehkan. Perbedaan ini disebabkan oleh pendekatan metodologis yang berbeda dalam mengevaluasi dalil-dari syariat. Penelitian ini bertujuan untuk mengkaji ulang secara kritis landasan hukum di balik larangan tersebut dengan menganalisis secara komprehensif ayat-ayat al-Qur'an dan hadits yang relevan. Menggunakan metode penelitian kepustakaan kualitatif dengan analisis isi dan komparatif, penelitian ini meneliti sanad dan matan hadits-hadits yang sering dijadikan dalil larangan. Temuan penelitian menunjukkan bahwa ayat al-Qur'an (QS. al-Nisa': 43) secara eksplisit membolehkan orang junub melewati masjid tanpa membahas bacaan al-Qur'an, sementara tidak ada larangan jelas dari al-Qur'an bagi wanita haid. Secara kritis, hadits-hadits yang melarang perbuatan ini mengandung kelemahan signifikan, termasuk perawi yang tergolong majhul (tidak dikenal), matruk (ditinggalkan), atau tidak terpercaya, seperti Aflat bin Khalifah dan Abdillah bin Salamah. Konsekuensinya, hadits-hadits ini dinilai lemah (da'if) dan tidak layak dijadikan landasan hukum. Penelitian menyimpulkan bahwa wanita haid diperbolehkan masuk masjid dan membaca al-Qur'an, sementara orang junub hanya diperbolehkan melewati masjid. Penelitian merekomendasikan agar ulama memprioritaskan sumber-sumber otentik dan secara ketat menerapkan kaidah al-jarh muqaddamun ala al-ta'wil (celaan didahulukan daripada pujian) dalam mengevaluasi riwayat yang kontradiktif.